Bencana Teknologi yang Berkembang Pesat Dalam Novel Life Hack Karya Perry June - Saputro, Muhammad Rifqi Firdaus; Ramadani, Irsyad Alif; Kurniawan, Eva Dwi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The research aims to see and develop how the use of technology can influence human life in the future. The emergence of artificial intelligence technology has made humans understand the importance of technological development and how we respond to it because it is us who will process and develop this technology. This research uses a qualitative descriptive method where the author states that technology has a very important role in the future of human life. The various impacts resulting from the creation of technology in this novel will make readers understand how big the impact of this technology will be on humans in the future.